Beyond inflammation: metabolic implications of biological and TsDMARD therapies in dermatologic and rheumatologic diseases - Corrao, Salvatore; Scibetta, Salvatore; Pardo, Nicola; Cangemi, Ignazio; Mirarchi, Luigi; Corrao, Giacomo; Amodeo, Simona; Calvo, Luigi (Frontiers in Immunology, 2026)
Biologic and targeted synthetic disease-modifying antirheumatic drugs (DMARDs) have transformed the management of chronic inflammatory diseases. Yet their therapeutic impact extends beyond cytokine suppression, influencing systemic metabolic pathways that are increasingly recognised as central to immune regulation. This narrative review examines the immunometabolic effects of major biologic and targeted synthetic DMARD classes used in dermatologic and rheumatologic diseases. We synthesise evidence on how these agents modulate insulin sensitivity, lipid metabolism, adipokine profiles, mitochondrial function, and adipose-tissue inflammation thereby shaping cardiovascular and metabolic risk. TNF inhibitors show heterogeneous metabolic effects, whereas IL-6 blockade and JAK inhibition consistently improve glycemic parameters despite inducing characteristic lipid changes. IL-17 and IL-23 inhibitors may attenuate adipose inflammation, while TYK2 inhibitors appear metabolically neutral. Through integration of mechanistic insights and clinical data, this review highlights the need to incorporate metabolic phenotyping into therapeutic decision-making. Understanding the distinct metabolic fingerprints of DMARDs may enable more precise patient stratification and support emerging combinatorial strategies with metabolic agents such as GLP-1 receptor agonists and SGLT2 inhibitors. These perspectives underscore the translational importance of viewing DMARD therapies not only as immunomodulators but also as systemic metabolic regulators.